Fusogenic liposomes and their suitability for gene delivery. (December 2006) - Yoshikawa, Tomoaki; Okada, Naoki; Nakagawa, Shinsaku
A novel carrier system to deliver large exogenous molecules into the cytosol has advantages for efficient delivery compared with traditional transfection techniques. We previously prepared a fusogenic liposome (FL) system by fusing phospholipid-based conventional liposomes with ultraviolet inactivated Sendai virus, which possess membrane fusion activity derived from the Sendai virus accessory protein. The FLs deliver their contents rapidly and directly into the cytoplasm rather than by endocytosis via membrane fusion without cytotoxicity. This FL-mediated cytoplasmic delivery technique is a powerful tool with the potential for wide use in the field of gene regulation and for the development of gene therapy. This review focuses on the suitability of FLs as a versatile and effective gene delivery system.